2014
DOI: 10.18632/oncotarget.1988
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ING1 levels in breast cancer promotes metastasis

Abstract: INhibitor of Growth 1 (ING1) expression is repressed in breast carcinomas, but its role in breast cancer development and metastasis is unknown. ING1 levels were quantified in >500 patient samples using automated quantitative fluorescence immunohistochemistry, and data were analysed for correlations to patient outcome. Effects of altering ING levels were examined in microarrays and metastasis assays in vitro, and in a mouse metastasis model in vivo. ING1 levels were lower in tumors compared to adjacent normal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 40 publications
3
18
1
Order By: Relevance
“…Like as previous studies in Iran, median age of breast cancer patients at the time of diagnosis was lower than in developed countries (Korizumi et al, 2010;Khodabakhshi et al, 2011;Thakur et al, 2014).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Like as previous studies in Iran, median age of breast cancer patients at the time of diagnosis was lower than in developed countries (Korizumi et al, 2010;Khodabakhshi et al, 2011;Thakur et al, 2014).…”
Section: Discussionsupporting
confidence: 66%
“…For metastasis to occur cancer cells have to attain a specific genotype and epigenotype, which allows them to disseminate from the primary tumor mass, survive, and then proliferate at secondary sites. Breast cancer cells have a distinct epigenomic DNA methylation profile which affects their metastatic potential (Thakur et al, 2014). Recent reports have shown that C-X-C chemokine receptor 4, TNF-α and IL-6 play an important role in metastasis (Tripsianis et al, 2013;Jiyang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…ING1 protein level was measured using quantitative fluorescence immunohistochemistry on the HistoRx AQUA® platform in breast cancer patient samples from the Calgary Tamoxifen cohort as described previously [ 31 ]. The specificity of the ING1 monoclonal antibody used for fluorescence IHC was assessed in HEK293 cells and placental tissue Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other members of the ING family, and in particular ING4, have also been reported to be down-regulated in breast cancers with a dominant mutant allele of the ING4 gene promoting tumor growth [ 29 , 30 ]. Recently, we reported that reduced ING1 levels are correlated with increased metastasis in breast cancer patients [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain qualitative assessments of bone osteolysis caused by metastasis, micro-computed tomography (μCT40, Scanco Medical) was used as previously described [ 32 , 34 ]. To examine angiogenesis of a metastatic site, mouse were terminally perfused with a radio-opaque silicone rubber (Microfil, Flow Tech) to form a radio-opaque vascular cast that can be visualized using μCT as we have previously described [ 35 ].…”
Section: Methodsmentioning
confidence: 99%